Penerapan Pendekatan Positive Deviance dalam Menanggulangi Masalah Malnutrisi pada Balita Melalui Program Pos Gizi - Ayubi, Dian; Rahayu, Nurdianaturrahma Budi; Yulianti, Y (FKM - UNEJ, 2013)
More than half of infant and under five children mortality is caused by malnutrition. Possitive deviance approach is widely used to increase nutrition status of children. This study was aimed to increase nutrition status among underfive children through âPos Giziâ intervention. This pre-experimental study design involved 20 mothers and their under five year children. âPos Giziâ intervention covered counseling, training and education. Data collection was used self-administered quetionnaires. After the intervention, the study found nutrion status of 70% children increases as well as knowledge of mothers. Home re-visitation should be regularly conducted to monitor and to motivate mothers in improving nutriotion status.